2011
DOI: 10.1007/s12122-011-9118-5
|View full text |Cite
|
Sign up to set email alerts
|

Firm Size and Work-Related Training: New Evidence on Incidence, Intensity, and Training Type from Australia

Abstract: Job training, Firm size-training effects, Australian labor markets,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…As found in other research on training incidence, the rate of training increases as job tenure increases (Bartel 1995;loewenstein and spletzer 1997;waddoups 2012). In terms of the decline in the incidence of training over the period, however, the rates are fairly uniform across job-tenure categories.…”
Section: Education Age and Job Tenuresupporting
confidence: 58%
See 1 more Smart Citation
“…As found in other research on training incidence, the rate of training increases as job tenure increases (Bartel 1995;loewenstein and spletzer 1997;waddoups 2012). In terms of the decline in the incidence of training over the period, however, the rates are fairly uniform across job-tenure categories.…”
Section: Education Age and Job Tenuresupporting
confidence: 58%
“…Managers and workers in the professional and technical jobs showed the largest absolute declines in training, and production workers the largest percentage decline. workers in large firms and those covered by a union contract are the most likely to receive training, so it is not surprising that in absolute terms their training incidence fell more than the incidence of those employed in smaller firms and who were not union covered (e.g., Booth et al 2003;waddoups 2011;waddoups 2014a). The percentage decline from 2001 to 2009, however, is very similar across the categories, ranging from 26% for workers in small firms to 33% for those in larger firms.…”
Section: Occupation Union Status and Firm Sizementioning
confidence: 99%
“…Finally, previous literature suggests that organizational, occupational and personal characteristics can influence the chances employees get for increasing their employability in the workplace (De Vries et al ., ; Van der Heijden et al ., ). Evidence suggests that investments in formal training are higher in larger companies (Waddoups, ), and in high technology and knowledge‐intensive sectors (Marzec et al ., ). Furthermore, the most varied employability practices were found in the smallest firms where work design often allows an higher degree of job enrichment, task rotation and job enlargement (Patton et al ., ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Hoque and Bacon (2006) found the same result even within their SME sample. Waddoups (2011) found that much less training occurs in firms with fewer than ten workers.…”
Section: Hypothesis 11: Firm Age Has a Positive Effect On Organizatimentioning
confidence: 99%